Analysis procedure for earthquake resistant structures - Hejazi, Farzad; Karimzade, Keyhan (Springer, 2018)
This book presents an analysis procedure for structures that are exposed to the lateral loads such as earthquake and wind. It includes the process for calculating and distributing the effective load into structural elements, as well as for calculating the displacements for different types of structures, e.g. reinforced concrete and steel framed structures. The book provides civil engineers with clear guidelines on how to perform seismic analysis for various building systems, and how to distribute the lateral load to the structural components. This book consists of 4 chapters: The first chapter offers an introduction, while Chapter 2 discusses moment resistance frame. The final two chapters explore shear wall frames and brace frames respectively. Each chapter follows the same structure, explaining step by step all the necessary algorithms, equations and procedures for calculating 1) loads, 2) the centre of mass, 3) stiffness of structures, 4) centre of stiffness, 5) lateral loading, 6) the distribution of lateral loads, and 7) the lateral displacement. Demonstrating the implementation of real building analysis, the book provides architectural drawings and structural plans at the beginning of each chapter.